GALLIUM-68 PURIFICATION - LE, VAN SO (2017)
A method is described for obtaining purified 68Ga. The method comprises eluting 68Ga from a sorbent in and/or on which are sorbed 68Ga and 68Ge, so as to generate a crude 68Ga solution. The sorbent should have a higher affinity for 68Ge than for 68Ga. The crude 68Ga solution is then applied to a medium cation exchange resin, and the resin is eluted with an aqueous alcohol so as to retain the 68Ga on the resin and remove unwanted species from the resin. The resin is then eluted with an eluent, which may be an acidic solution, an alkaline solution or a solution of a species capable of complexing 68Ga ions, so as to obtain an eluate comprising purified 68Ga ions.